Enhanced extraction of phenolic compounds from coffee industry’s residues through solid state fermentation by Penicillium purpurogenum - García, Lady Rossana Palomino [UNESP]; Biasetto, Carolina Rabal [UNESP]; Araujo, Angela Regina [UNESP]; del Bianchi, Vanildo Luiz [UNESP] (FapUNIFESP (SciELO), 2015)
The use of agroindustrial residues is an economical solution to industrial biotechnology. Coffee husk and pulp are abounding residues from coffee industry which can be used as substrates in solid state fermentation process, thus allowing a liberation and increase in the phenolic compound content with high added value. By employing statistical design, initial moisture content, pH value in the medium, and the incubation temperature were evaluated, in order to increase the polyphenol content in a process of solid state fermentation by Penicillium purpurogenum. The main phenolic compounds identified through HPLC in fermented coffee residue were chlorogenic acid, caffeic acid, and rutin. Data obtained through HPLC with the radical absorbance capacity assay suggest the fermented coffee husk and pulp extracts potential as a source of phenolic acids and flavonoids. Results showed good perspectives when using P. purpurogenum strain to enhance the liberation of phenolic compounds in coffee residues.
Keywords: Antioxidant activity; Bioprocess design; Chlorogenic acid; Coffee husk; Coffee pulp; Filamentous fungi